Acquisition of the English passive by L1 Malay ESL adult learners - Mahdun, Mahanum (2020)
The English passive is one of the problematic structures to be acquired by L2 learners from different L1 backgrounds. Second language acquisition studies have shown that L1 Malay ESL adult learners face difficulties in acquiring the English passive. This could be due to the varying competency levels among the L2 learners as well as cross-linguistic interferences from the learners’ L1, which is Malay language. The Interlanguage Hypothesis postulated that the L2 learner’s interlanguage (IL) system is characterised by systematicity, variability and permeability. L2 learners’ interlanguage grammar undergoes developmental stages in the acquisition process, influenced by their L1 and L2, particularly learners at the initial stages of acquisition. Hence, this study aims to study the acquisition of the English passive by L1 Malay ESL adult learners in Malaysia by investigating the IL representations of the English passive at four different levels of proficiency: Elementary, Lower Intermediate, Upper Intermediate and Advanced. 499 L1 Malay ESL adult learners from randomly selected higher learning institutions in Malaysia participated in the study. Firstly, the respondents completed a background questionnaire (BQ) and a placement test (Oxford Placement Test). The results of the OPT determines the respondents’ proficiency groups. Subsequently, a Grammaticality Judgement Task (GJT) and a Picture Description Task (PDT) were administered to examine the respondents’ underlying knowledge and production of the English passive. The data were tabulated and described using frequency distribution and analysed using paired T-tests and one-way ANOVA. The results indicated that most of the L1 Malay ESL adult learners have acquired the English passive. However, their competency level was non-native like, even for the Advanced group. Their judgements on the grammaticality of the test items were indeterminate, particularly those at the lower proficiency levels. In terms of unaccusativity, it was observed that the learners were inclined to overgeneralise the passive morphology the English intransitive verbs; the unaccusative verbs (UAV) and unergative verbs (UEV). The overgeneralisation was higher with the UAV than the UEV and this might be due to the similar underlying representations of the UAV and the passive verb. It seems like the learners were sensitive to the distinction between UAV and UEV, as indicated by the significantly higher overpassivisation errors with the UAV. Besides, the results also indicated that the main errors committed by the L1 Malay ESL adult learners are related to omission of the be verb, incorrect past participle forms and incorrect SVA. It is suggested that these errors could be due to the absence of the be verb, and the [+/-tense] and [+/-agreement] features in the Malay language. This study concludes that the L1 Malay ESL adult learners have not fully acquired the English passive and there is a significant difference among the proficiency groups in their performance on the English passive. The L1 Malay ESL adult learners also tend to overpassivise the UAV more than the UEV. Furthermore, these learners produced interlingual and intralingual errors in their acquisition of the English passive. The findings of this study sheds light into the IL representations of the English passive in the language acquisition/learning process of the L1 Malay ESL adult learners. This contributes insights to the SLA literature, particularly the Interlanguage and Unaccusative Hypotheses. In addition, the findings would have pedagogical implications for the English as a second language (ESL) classroom.